Larangan Riba dalam Hadits di Era Digital - Arum, Hafidza Sanshia; Muzan, Amrul (Jurnal Iqtisaduna, 2024)
This study discusses the relevance of the prohibition of usury in the hadith in the digital era, focusing on the application of sharia principles in modern financial technologies such as fintech, cryptocurrency, and online lending. The purpose of the study is to explore the concept of usury in the hadith and identify its implications for the contemporary digital financial system. This research uses a qualitative method with a descriptive-analytical approach. Data collection was conducted through library research, using primary sources in the form of relevant hadith texts and secondary sources such as journal articles and books. The data were analyzed using a thematic approach to identify the relevance of the prohibition of usury in digital financial transactions. The results show that although digital financial technology offers wider financial inclusion, some financial products still have the potential to involve usury practices. The implications of this study include the need for stricter regulations, development of sharia-based fintech products, and improvement of public financial literacy. Thus, the prohibition of usury in the hadith remains relevant as a guide in facing the challenges of modern financial technology in order to achieve economic justice in accordance with sharia principles.